A low-temperature preparation method for single-phase multi-principal element ultra-high temperature ceramic nanopowder
By synthesizing transition metal nanooxide precursors using the sol-gel method and carbide reaction with the carbon source, the problem of difficulty in preparing multi-main single-phase carbide nano powders in the prior art is solved, and nano powders with particle size less than 100 nm are prepared under low temperature conditions, with simple process and high safety.
Patent Information
- Application Number
- CN202210444403.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-04-25
AI Technical Summary
The prior art is difficult to effectively prepare multi-main single-phase carbide nanopowders, especially under low temperature conditions, with complex processes and high risk, making it difficult to obtain nanopowders with particle sizes below 100 nm.
The nano-oxide precursor was synthesized by the sol-gel method by the synthesis of transition metal nanooxides and carbon thermal reduction method, and carbonization reaction with the carbon source in an inert atmosphere was obtained to obtain a single-phase multi-main ultra-high temperature ceramic nanopowder.
A single-phase multi-main ultra-high temperature ceramic nanopowder with a particle size less than 100 nm was prepared under low temperature conditions. The process is simple and safe, and is suitable for the multi-component single-phase carbide synthesis of most metal elements of Groups III, IV and VB.
Smart Images

Figure CN116986894B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of carbide ultra-high temperature ceramic powders, and in particular to a low-temperature preparation method of single-phase multi-principal-element ultra-high temperature ceramic nanopowders. Background Art
[0002] Ultra-high temperature ceramics are generally defined as materials with a melting point above 3000°C, an operating temperature above 2000°C, and a chemical composition of borides, carbides, and nitrides of transition metals of groups IV and VB. Among them, carbide ultra-high temperature ceramics are a type of material with a rock salt structure and a metal-to-carbon atomic ratio of 1:1, including titanium carbide, tantalum carbide, hafnium carbide, zirconium carbide, etc. This type of material has extremely strong covalent bonds inside, so its intrinsic melting point is extremely high. It is the material with the highest melting point known on Earth. It is widely used in industrial cutting tools, thermal structural components of aerospace vehicles, hypersonic vehicles and propulsion systems (such as missiles), cladding materials for fourth-generation nuclear reactors, etc., and has broad application prospects in the field of anti-oxidation and ablation of hypersonic vehicles.
[0003] The disadvantages of carbide ultra-high temperature ceramic materials are also prominent. They mainly include large intrinsic brittleness, difficulty in sintering and forming, and poor medium and low temperature oxidation resistance near 1000°C. Moreover, they have poor ablation resistance in ultra-high temperature extreme service environments, and the oxide layer structure after ablation is loose and easily mechanically eroded and peeled off, resulting in a significant reduction in the mechanical properties of the material after oxidation ablation, limiting its application as a high-temperature structural material in extreme environments.
[0004] The synthesis of multi-component single-phase nanopowders of carbides plays a key role in solving the above problems. First, the synthesized nanopowders can be sintered to obtain blocks with finer grains; in the field of materials science, finer grains often mean more grain boundaries, higher strength and toughness; and nanopowders have good fluidity and are easier to spray into coatings. Secondly, ceramic sintering is a process that consumes the surface energy of the powder to grow the grains and densify the blocks; and carbide nanopowders have a larger specific surface area than micron powders, that is, higher surface energy, so they can reduce the sintering temperature and save energy. Finally, multi-component carbides have obvious advantages in anti-oxidation and ablation performance compared to single-component carbides, because the multi-component metals have a synergistic effect in the oxidation process to form a dense oxide intermediate layer or carbon oxide transition layer, and single-phase ceramics will not produce cracks due to thermal mismatch when serving at high temperatures, leading to oxidation failure or fracture failure, thereby greatly improving the anti-oxidation and ablation performance of carbides.
[0005] The carbonization reduction method is currently one of the simplest and most common methods for preparing carbide powder. The currently reported methods for synthesizing carbide powder by carbonization reaction have the following disadvantages: 1. The carbonization temperature is high and the powder particle size is large. For example, Chinese patents 202010171717.8 (a rare earth-containing carbide high-entropy ceramic precursor and high-entropy ceramic and preparation method) and 202011448224.0 (a high-entropy absorbing carbide ceramic powder material, preparation method and application thereof), the temperature for forming multi-principal single-phase carbides is not less than 1600°C, so that the metal elements are fully dissolved into a single phase, which causes the powder particles to agglomerate or grow abnormally, and it is difficult to obtain nanoparticles with smaller particle size; 2. The process flow is complicated and highly dangerous. For example, Chinese patent 202011450491.1 (a high-performance (TiTaHfZrNb)C high-entropy carbide ceramic and its preparation method) requires multiple steps including ball milling and multi-step heat treatment, and when the sintering temperature is 1800-2000°C, it needs to be assisted by a pressure of 30-50MPa; another example is Chinese patent 202111007346.0 (a (ZrTiCoNb)C high-entropy carbide ceramic material and its preparation method) at a sintering temperature of 1200-2000°C, it needs to be assisted by 2.45GHz microwaves. Therefore, a simple low-temperature method for stably and reliably preparing multi-principal single-phase carbide nanopowders is particularly important. Summary of the invention
[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a low-temperature preparation method for single-phase multi-principal component ultra-high temperature ceramic nanopowders, which has good single-phase properties, a particle size of the synthesized powder is below 100nm, the synthesis method is safe, stable and controllable, and the synthesis temperature is significantly lower than other methods.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] This scheme consists of two parts, the first part is the synthesis of transition metal nanoparticles, and the second part is the carbon thermal reduction of transition metal oxides. The synthesis of oxide nanoparticles helps to reduce the temperature of the carbon thermal reduction reaction in the second step. The temperatures of both steps are lower than those of other methods, as follows:
[0009] A low-temperature preparation method for single-phase multi-principal-element ultra-high temperature ceramic nanopowder, the method comprising the following steps:
[0010] (1) Synthesis of transition metal nano-oxide precursor: Inorganic / organic metal salt and reaction solvent are used as initial reactants, mixed evenly in a reaction kettle, heated to perform sol-gel reaction, and then cooled; the sol-gel reaction product is separated, washed and dried to obtain a transition metal nano-oxide precursor;
[0011] (2) Carbothermal reduction of transition metal oxides: The transition metal nano-oxide precursor and the carbon source are mixed evenly, heated in an inert atmosphere for carbonization reaction, and cooled to obtain a single-phase multi-principal ultra-high temperature ceramic nano-powder. The mass ratio of the transition metal nano-oxide precursor to the carbon source is 1:(3-6).
[0012] Furthermore, the metal is a transition metal or a rare earth metal, including one or more of Hf, Zr, Ti, Ta, La, Ce, Nb or Y.
[0013] Furthermore, the organic group includes isopropanol, acetylacetonate, acetate or aromatic groups, and the inorganic group includes Cl, Br or I.
[0014] Furthermore, the reaction solvent includes ethers, alcohols, ketones, acids, amines or aldehydes.
[0015] Furthermore, the reaction solvent includes benzyl alcohol, benzoic acid, anisole, oleic acid, oleylamine or trioctylphosphine oxide.
[0016] Furthermore, the procedure of the sol-gel reaction is: heating from room temperature to 200-300°C at a heating rate of 5°C / min, then keeping the temperature for 24-96 hours, and finally cooling to room temperature at a cooling rate of 5°C / min.
[0017] Furthermore, the carbon source is polysaccharide or / and monosaccharide or / and resin or / and carbon black.
[0018] Furthermore, the carbon source includes glucose, sucrose, fructose or phenolic resin.
[0019] Furthermore, the procedure of the carbonization reaction is: first increase the temperature from room temperature to 1200°C at a heating rate of 5°C / min, then increase the temperature from 1200°C to the target temperature at a heating rate of 2°C / min, then keep the temperature for 1-5h, and finally cool to room temperature at a cooling rate of 5°C / min.
[0020] Furthermore, the target temperature is 1500-2000°C.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The preparation process of the present invention is simple, and the reaction is mild and controllable. The initial reactants involved are inorganic / organic metal salts and reaction solvents, which are both easily available commercial drugs. Due to the presence of organic groups, the reaction kinetics of the reaction is slow and mild, thereby improving safety;
[0023] (2) The reaction temperature of the present invention is low and the powder size is small. Both the precursor synthesis temperature and the carbonization reaction temperature are lower than those of the known methods, which is conducive to reducing reaction costs and saving energy. Moreover, the oxide precursor is only 3-5nm, and the carbide powder size is less than 100nm, which has great advantages in both spraying and sintering densification;
[0024] (3) The present invention has wide applicability, uniform distribution of each component, and low content of second phase. The present method can be applied to the synthesis of multi-component single-phase carbides of most metal elements of groups III, IV and VB, including some rare earth elements. Each component is uniformly distributed in the carburized product without segregation. Reasonable control of the amount of carbon source added can minimize the residue of second phase oxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the morphology of the oxide precursor in Example 1;
[0026] Figure 2 The morphology of the multi-component carbide in Example 1;
[0027] Figure 3 is the XRD spectrum of the multi-component carbide in Example 1;
[0028] Figure 4 This is an element distribution analysis diagram of the multi-component carbide in Example 1. DETAILED DESCRIPTION
[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0030] A low-temperature preparation method for single-phase multi-principal element ultra-high temperature ceramic nanopowder
[0031] 1. Synthesis of transition metal nanooxides
[0032] The synthesis of transition metal nano-oxides adopts the sol-gel method, and the specific chemical process is as follows:
[0033] Inorganic / organic metal salts and reaction solvents are used as initial reactants, and the initial reactants are mixed evenly in the polytetrafluoroethylene reactor lining at room temperature. If the metal salt needs to be dissolved, it can be heated appropriately, and the temperature does not exceed 60°C. The reactor is sealed and placed in a high-temperature drying oven. The temperature is raised from room temperature to 200-300°C at a heating rate of 5°C / min. This process takes about 40-60 minutes, and then kept warm for 24-96 hours. Finally, it is cooled to room temperature with the furnace at a cooling rate of 5°C / min. The metal can be a transition metal or rare earth metal element such as Hf, Zr, Ti, Ta, La, Ce, Nb, Y, etc.; the organic group can be an isopropanol group, an acetylacetonate group, an acetic acid group, an aromatic group, etc., and the inorganic group can be Cl, Br, I, etc. The inorganic / organic metal salt is a free combination of metal and organic or inorganic parts. Generally, the state of inorganic / organic metal salts is solid powder, and a small part is liquid such as titanium tetraisopropoxide. The reaction solvent is a variety of organic solvents, including ethers, alcohols, ketones, acids, amines and aldehydes. One or more of them are used in the reaction. Common ones are benzyl alcohol, benzoic acid, anisole, oleic acid, oleylamine, trioctylphosphine oxide, etc. The standard of free combination is the types of metal elements contained in the target carbide and whether their reaction progress can match each other. If they do not match or the gap is large, single-phase carbide cannot be formed. Generally, the trial and error method of preliminary experiments is used to determine whether the reaction progress between the metal salts matches each other.
[0034] The sol-gel reaction product is taken out, placed in a centrifuge tube, an organic solvent is added for washing, and then placed in a centrifuge for centrifugal operation. After the centrifugation is completed, the washing waste liquid is poured out, and the washing and centrifugation operations are repeated at least 3 times. The final product is placed in a drying oven to dry to obtain an oxide precursor. The organic solvents for washing include ethanol, isopropanol, ether, chloroform, etc., among which ether and chloroform are preferred. In the centrifugal operation, the centrifugal test tube is preferably 50mL, the centrifugal speed is not less than 10000rpm, the centrifugal time is 5-20min, and the drying temperature is 60-120°C.
[0035] 2. Carbothermal reduction of transition metal oxides
[0036] The precursor prepared in step 1 is mixed evenly with the carbon source in a certain proportion by solid phase or liquid phase mixing, and placed in a graphite crucible, and the crucible is placed in a drying oven for preheating. The preheated crucible is then placed in a tubular furnace, and reacted in flowing argon gas, first at a heating rate of 5°C / min from room temperature to 1200°C, then at a heating rate of 2°C / min from 1200°C to the target temperature, then kept warm for 1-5 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min to obtain the target product.
[0037] The carbon source is various polysaccharides, monosaccharides and / or resins and carbon black, such as glucose, sucrose, fructose, phenolic resin, etc. The ratio of the precursor to the carbon source is determined by trial and error. If less carbon source is added, the carbonization is incomplete, and if more carbon source is added, dicarbide may be produced, depending on the metal element. The preheating temperature depends on the carbon source. The purpose of preheating is to reduce the generation of gas byproducts by the carbon source during the heating process of the tubular furnace, which affects the mixed state of the carbon thermal reduction reactants before reaching the target temperature. Therefore, the preheating temperature is determined by the thermal analysis results of the carbon source, but does not exceed 400°C, or no preheating is required. The argon gas flow rate is 0.05-1L / min, preferably 0.2L / min. The target temperature is 1500-2000°C, and generally 1600°C can complete the carbonization reaction. The target product is a multi-component single-phase carbide nanopowder.
[0038] Example 1
[0039] Acetylacetonate salts of four elements Hf, Zr, Ce, and La, titanium tetraisopropoxide, and benzyl alcohol were used as initial reactants. The initial ratio of the five metal salts was: 1.2 g of hafnium acetylacetonate, 1 g of zirconium acetylacetonate, 0.9 g each of cerium acetylacetonate and lanthanum acetylacetonate, 0.6 g of titanium tetraisopropoxide, and 50 mL of benzyl alcohol. The initial reactants were mixed evenly in a polytetrafluoroethylene reactor liner at room temperature. The reactor was sealed and placed in a high-temperature drying oven. The temperature was raised from room temperature to 220°C at a heating rate of 5°C / min, then kept warm for 24 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min.
[0040] Take out the sol-gel reaction product, place it in a 50mL centrifuge tube, add chloroform for washing, and then place it in a centrifuge for centrifugation. The centrifugation parameters are 10000rpm, 10min; after the centrifugation, pour out the washing waste liquid. Repeat the washing and centrifugation operation twice. Add ether and repeat once, for a total of 3 times. Place the final product in a drying oven and dry it at 80°C to obtain an oxide precursor. The morphology of the oxide precursor is as follows Figure 1 As shown, its particle size is only 3-5nm.
[0041] The oxide precursor and glucose were mixed evenly by solid phase mixing at a mass ratio of 1:5, and placed in a graphite crucible. The crucible was placed in a drying oven and preheated at 200°C for 24 hours. The preheated crucible was then placed in a tubular furnace and reacted in flowing argon. The temperature was first increased from room temperature to 1200°C at a rate of 5°C / min, and then increased from 1200°C to 1600°C at a rate of 2°C / min. The temperature was then kept at this temperature for 5 hours, and finally cooled to room temperature with the furnace at a rate of 5°C / min. A five-component single-phase carbide nanopowder was obtained, and its morphology is as follows: Figure 2 As shown in Figure 1, its particle size is only about 15nm. Its XRD spectrum is shown in Figure 1 Figure 3As shown in the figure, it can be seen that except for trace amounts of residual oxides, the powder has good single-phase properties. Figure 4 As shown, it can be seen that the element distribution is uniform at the nanoscale.
[0042] Example 2
[0043] Acetylacetonate salts of four elements Hf, Zr, Ta, and Y, titanium tetraisopropoxide, and benzyl alcohol were used as initial reactants. The initial ratio of the five metal salts was: 1.2 g of hafnium acetylacetonate, 0.8 g of yttrium acetylacetonate, 1 g each of tantalum acetylacetonate and zirconium acetylacetonate, 0.6 g of titanium tetraisopropoxide, and 50 mL of benzyl alcohol. The initial reactants were mixed evenly in a polytetrafluoroethylene reactor liner at room temperature. The reactor was sealed and placed in a high-temperature drying oven. The temperature was raised from room temperature to 270°C at a heating rate of 5°C / min, then kept warm for 48 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min.
[0044] The sol-gel reaction product was taken out, placed in a 50 mL centrifuge tube, and washed with ether, and then placed in a centrifuge for centrifugation at 10,000 rpm for 15 min. After the centrifugation, the waste liquid was discarded. The washing and centrifugation operations were repeated 3 times. The final product was placed in a drying oven and dried at 80°C to obtain an oxide precursor.
[0045] The oxide precursor and glucose were mixed evenly by liquid phase mixing at a mass ratio of 1:6, placed in a graphite crucible, and the crucible was placed in a drying oven and preheated at 80°C for 24 hours. The preheated crucible was then placed in a tubular furnace and reacted in flowing argon gas, first at a heating rate of 5°C / min from room temperature to 1200°C, then at a heating rate of 2°C / min from 1200°C to 1600°C, then kept warm for 5 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min, to obtain a five-component single-phase carbide nanopowder.
[0046] Example 3
[0047] Acetylacetonate salts of Hf, Zr and Ti and benzyl alcohol were used as initial reactants. The initial ratio of the five metal salts was: 1.2 g of hafnium acetylacetonate, 1 g of zirconium acetylacetonate, 0.6 g of titanium acetylacetonate, and 50 mL of benzyl alcohol. The initial reactants were mixed evenly in a polytetrafluoroethylene reactor liner at room temperature. The reactor was sealed and placed in a high-temperature drying oven. The temperature was raised from room temperature to 200°C at a heating rate of 5°C / min, then kept warm for 96 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min.
[0048] The sol-gel reaction product was taken out, placed in a 50 mL centrifuge tube, washed with chloroform, and then placed in a centrifuge for centrifugation at 10,000 rpm for 20 min. After the centrifugation, the waste liquid was discarded. The washing and centrifugation operations were repeated 3 times. The final product was placed in a drying oven and dried at 80° C. to obtain an oxide precursor.
[0049] The oxide precursor and carbon black are mixed evenly by solid phase mixing at a mass ratio of 1:3 and placed in a graphite crucible. The crucible is then placed in a tubular furnace and reacted in flowing argon gas, first at a heating rate of 5°C / min from room temperature to 1200°C, then at a heating rate of 2°C / min from 1200°C to 1600°C, then kept warm for 5 hours, and finally cooled to room temperature with the furnace at a cooling rate of 5°C / min, to obtain a three-component single-phase carbide nanopowder.
[0050] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A low-temperature preparation method of single-phase multi-principal-element ultra-high temperature ceramic nanopowder, characterized in that: The method comprises the following steps: (1) Synthesis of transition metal nano-oxide precursor: Inorganic and / or organic metal salts and reaction solvents are used as initial reactants, mixed evenly in a reaction kettle, heated to perform sol-gel reaction, and then cooled; the sol-gel reaction product is separated, washed and dried to obtain a transition metal nano-oxide precursor; (2) Carbothermal reduction of transition metal oxides: The transition metal nano-oxide precursor is mixed with a carbon source, heated in an inert atmosphere for carbonization reaction, and cooled to obtain a single-phase multi-principal component ultra-high temperature ceramic nano-powder; The metal in the metal salt includes two or more of Hf, Zr, Ti, Ta, La, Ce, Nb or Y; The reaction solvent includes ethers, alcohols, ketones, acids, amines or aldehydes; The carbon source is polysaccharide or / and monosaccharide or / and resin or / and carbon black; The temperature of the carbonization reaction is 1500-2000°C, and the particle size of the synthesized powder is below 100 nm.
2. The low-temperature preparation method of a single-phase multi-principal-element ultra-high temperature ceramic nanopowder according to claim 1, characterized in that: The organic group in the organic metal salt includes isopropanol, acetylacetonate, acetate or aromatic groups, and the inorganic group in the inorganic metal salt includes Cl, Br or I.
3. The low-temperature preparation method of a single-phase multi-principal-element ultra-high temperature ceramic nanopowder according to claim 1, characterized in that: The reaction solvent includes benzyl alcohol, benzoic acid, anisole, oleic acid, oleylamine or trioctylphosphine oxide.
4. The low-temperature preparation method of a single-phase multi-principal-element ultra-high temperature ceramic nanopowder according to claim 1, characterized in that: The procedure of the sol-gel reaction is: heating from room temperature to 200-300° C. at a heating rate of 5° C. / min, then keeping the temperature for 24-96 hours, and finally cooling to room temperature at a cooling rate of 5° C. / min.
5. The low-temperature preparation method of a single-phase multi-principal-element ultrahigh-temperature ceramic nanopowder according to claim 1, characterized in that: The carbon source includes glucose, sucrose, fructose or phenolic resin.
6. The low-temperature preparation method of a single-phase multi-principal-element ultrahigh-temperature ceramic nanopowder according to claim 1, characterized in that: The procedure of the carbonization reaction is: first increase the temperature from room temperature to 1200°C at a heating rate of 5°C / min, then increase the temperature from 1200°C to 1500-2000°C at a heating rate of 2°C / min, then keep the temperature for 1-5 h, and finally cool to room temperature at a cooling rate of 5°C / min.
Citation Information
Patent Citations
A rare-earth-containing carbide high-entropy ceramic precursor, high-entropy ceramic, and preparation method
CN111303581B
High-performance high-entropy (VNbTaMoW)C carbide ceramic and preparation method thereof
CN112441837A
High-performance (TiTaHfZrNb) C high-entropy carbide ceramic and preparation method thereof
CN112457017A
(ZrTiCoNb) C high-entropy carbide ceramic material and preparation method thereof
CN113582696A
Carbide high-entropy ceramic precursor containing rare earth, high-entropy ceramic and preparation method
CN111303581A